Analysis Of The Relationship Between Product Innovation And Electronic Word Of Mouth (E – WOM) On Buying Interest. (Study Of Consumer Survey Of Jajanan Kita Brand In Harapan Mulia, Kemayoran) - Istifa Ramadani; Koerniawan Hidajat (UNIVED Press, 2026)
This research aims to find out the relationship between product innovation and E-WOM on consumer buying interest, focusing on the Jajanan Kita brand located in Harapan Mulia, Kemayoran. Innovate products that will be highlighted in their marketing strategies, especially in the food industry. In the digital age, individuals, particularly young adults, rely more on social media to receive more data and recommendations. E – WOM refers to the information and recommendations provided by the client through an online platform to prove an effective response. Consumers no longer rely solely on ads due to the ease of access to recommendations and reviews of other buyers. This analysis applies Structural Equation Modelling and Partial Least Square to test the Research Model. The results of the analysis show that product innovation and E-WOM statistically and significantly affect consumer purchase intentions. This research, it is anticipated, can help those in the industry make important conclusions about marketing strategies, while also adding information about the importance of innovation and E-WOM to the food industry. Furthermore, this research can be applied as a basis for conducting more comprehensive investigations and to provide relevant empirical data to promote the development of local food stall businesses.